Voices around us: memory and community empowerment in reconstruction efforts in Colombia - Ruiz Romero, Gabriel (International journal of transitional justice, 2012)
Although the Colombian armed conflict has had the most impact in the countryside, rural communities have had only a marginal role in the development of state policies designed to address the effects of violence. Seeking to overcome such marginalization, peasant women victims of the armed conflict from Granada came together to address this imbalance and preserve the memory of their dead and missing relatives. They formed the Asociación de Víctimas de Granada and launched the project, Salón del Nunca Más (Hall of Never Again). This Notes from the Field piece explores the association’s strategies to conserve memory and offers some preliminary observations on the outcomes of the self-healing process within this community.